2015
DOI: 10.2903/j.efsa.2015.4211
|View full text |Cite
|
Sign up to set email alerts
|

Conclusion on the peer review of the pesticide risk assessment for bees for the active substance imidacloprid considering all uses other than seed treatments and granules

Abstract: The European Food Safety Authority (EFSA) was asked by the European Commission to perform a risk assessment of neonicotinoids, including imidacloprid, as regards the risk to bees, as a follow up of previous mandates received from the European Commission on neonicotinoids. In this context the conclusions of EFSA concerning the risk assessment for bees for the active substance imidacloprid are reported. The context of the evaluation was that required by the European Commission in accordance with Article 21 of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…When the field was pretreated with 1 mg/L of OTC, the residue of olefin-IMI also increased. According to the EFSA report, olefin-IMI was an high toxic metabolite of IMI . Those results showed that OTC increased the residue of olefin-IMI, which might lead to a higher environmental risk.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the field was pretreated with 1 mg/L of OTC, the residue of olefin-IMI also increased. According to the EFSA report, olefin-IMI was an high toxic metabolite of IMI . Those results showed that OTC increased the residue of olefin-IMI, which might lead to a higher environmental risk.…”
Section: Resultsmentioning
confidence: 98%
“…According to the EFSA report, olefin-IMI was an high toxic metabolite of IMI. 30 Those results showed that OTC increased the residue of olefin-IMI, which might lead to a higher environmental risk.…”
Section: Effect Of Otc On the Dissipation Of Imi In Soilmentioning
confidence: 96%